2012
DOI: 10.1111/j.1753-5131.2012.01056.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of the brain in farmed fish

Abstract: As is well known, optimal levels of both homeostasis and welfare of farmed fish are almost completely dependent upon human endeavour to investigate fish brain capacities and utilize them for the greatest benefit. According to the accumulated research experience specifically concerning minimization of farmed fish stress, the final outcome of the involved mechanisms is strongly associated with fish species and biological stage as well as a number of rearing environment parameters related to the type of the produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 78 publications
0
3
0
2
Order By: Relevance
“…Ten years later, Le Bail and Boeuf's review formulated hypotheses on mammalian hormones (e.g., leptin) that might putatively regulate feeding in fish (Le Bail and Boeuf, 1997). In the early twenty-first century, a number of reviews report recent advances on the field and include an increasing number of hormones (e.g., NPY, orexins, CART), some more comparative (Lin et al, 2000; de Pedro and Björnsson, 2001; Volkoff et al, 2005; Gorissen et al, 2006; Volkoff, 2011; Hoskins and Volkoff, 2012), some more focused on a single species (e.g., goldfish Matsuda, 2009; Matsuda et al, 2011a) or a particular group of fish (e.g., elasmobranchs Demski, 2012), some focused on growth (Won and Borski, 2013), and some on aquaculture and behavior (Papoutsoglou, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Ten years later, Le Bail and Boeuf's review formulated hypotheses on mammalian hormones (e.g., leptin) that might putatively regulate feeding in fish (Le Bail and Boeuf, 1997). In the early twenty-first century, a number of reviews report recent advances on the field and include an increasing number of hormones (e.g., NPY, orexins, CART), some more comparative (Lin et al, 2000; de Pedro and Björnsson, 2001; Volkoff et al, 2005; Gorissen et al, 2006; Volkoff, 2011; Hoskins and Volkoff, 2012), some more focused on a single species (e.g., goldfish Matsuda, 2009; Matsuda et al, 2011a) or a particular group of fish (e.g., elasmobranchs Demski, 2012), some focused on growth (Won and Borski, 2013), and some on aquaculture and behavior (Papoutsoglou, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Finally, it has to be concluded that, as long as fish brain is characterized by the lack of neocortex, its reactions to the environmental stimuli, including music, are depended almost entirely on each species evolutionary age existence level and biological stage, especially on their welfare demands, as well as on the way they try and succeed to ''enjoy'' themselves. Thus, it should be emphasized that fish, based on their brain skills, express their ''emotional'' demands using only their instinctual power, while humans, after some age, besides of the type of their emotional character, can also use their rationalism potential to make their life ''better'' (Fried et al 2001;Papoutsoglou 2012bPapoutsoglou , 2013Shao and Lee 2014;Winterer et al 2006). …”
Section: Discussionmentioning
confidence: 97%
“…In juveniles of many species, the RNA/DNA ratio also significantly influences fish growth and feeding (Myron et al 2003). Therefore, physiological factors are important determinants of the feeding habits of fish, but optimally satisfying the living ethology of farmed fish, as expressed by their nervous system, should also be carefully considered when developing a specific feeding control method or system (Papoutsoglou 2012).…”
Section: Factors Influencing Fish Feedingmentioning
confidence: 99%